2002
DOI: 10.1109/tnn.2002.804281
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the parameters of a neuro-genetic algorithm

Abstract: Abstract-Interest in hybrid methods that combine artificial neural networks (ANNs) and evolutionary algorithms (EAs) has grown in the last few years, due to their robustness and ability to design networks by setting initial weight values, by searching the architecture and the learning rule and parameters. However, papers describing the way genetic operators are tested to determine their effectiveness are scarce; moreover, few researchers publish the most suitable values of these operator parameters to solve a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Earlier studies have already shown that evolution can be used to create high performance neural network systems [2][3][4][5][6][7][8][9][10][11][12][13][15][16][17], and this paper has confirmed that even a less than optimal choice of evolutionary approach can still result in the emergence of good individual networks. However, it is now clear from this study that to generate the best possible neural networks, it is important to choose the right evolutionary approach for each particular application.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Earlier studies have already shown that evolution can be used to create high performance neural network systems [2][3][4][5][6][7][8][9][10][11][12][13][15][16][17], and this paper has confirmed that even a less than optimal choice of evolutionary approach can still result in the emergence of good individual networks. However, it is now clear from this study that to generate the best possible neural networks, it is important to choose the right evolutionary approach for each particular application.…”
Section: Discussionsupporting
confidence: 55%
“…There appear not to have been any general investigations into which evolutionary approaches are best to use for this, nor any checks for potentially deleterious side-effects of the evolution, though comparative studies of other factors do exist (e.g. [3,8,9,10,11]). This paper attempts to fill this gap, with particular emphasis on the potential pitfalls of the most obvious evolutionary approaches, and their associated solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the performance of the proposed method, the one-way analysis of variance (ANOVA) [5,10] was used. This statistical tool, based on the analysis of the mean variance, is widely used.…”
Section: Discussionmentioning
confidence: 99%
“…In structural evolution of an ANN, the network parameters such as the number of hidden layers/nodes, learning rates, momentum, are optimized (e.g., [18][19][20]). Occasionally, EAs are used for structural evolution whereas the ANN is responsible for weight adaptation through a suitable ANN training algorithm.…”
mentioning
confidence: 99%